Evaluation of DOAC Dipstick Test for Detecting Direct Oral Anticoagulants in Urine Compared with a Clinically Relevant Plasma Threshold Concentration. (March 2022) - Örd, Lenna; Marandi, Toomas; Märk, Marit; Raidjuk, Leonid; Kostjuk, Jelena; Banys, Valdas; Krause, Karit; Pikta, Marika
Measuring direct oral anticoagulant (DOAC) concentrations might be necessary in certain clinical situations but is not routinely performed. The DOAC Dipstick is a new rapid test for detecting DOACs in urine. The aim of this study was to evaluate the possible uses and limitations of the DOAC Dipstick and to compare visual analysis and DOASENSE Reader analysis of DOAC Dipstick pads. Plasma and urine samples were collected from 23 patients taking DOACs. DOAC concentrations in plasma and urine were measured by chromogenic substrate assays and in urine also by the DOAC Dipstick. Plasma concentrations were dichotomized at a threshold of ≥30 ng/mL. Patient samples were compared with samples from control individuals not using anticoagulants (n = 10) and with DOASENSE control urines. The Combur-10 test was used to measure parameters that may affect urine color and hence the interpretation of the DOAC Dipstick result. DOAC Dipstick test results were positive in 21/23 patient urine samples at a plasma DOAC concentration of ≥30 ng/mL and in 2/23 patient urine samples at a plasma DOAC concentration of <30 ng/mL. Inter-observer agreement was above 90% for visual analysis of patient urine samples and was 100% for DOASENSE Reader analysis of patient urines and for analysis of control group urines and DOASENSE control urines. Abnormalities in urine color detected by the Combur-10 test did not affect the DOAC Dipstick results. DOAC Dipstick detects DOACs in urine at a plasma threshold of ≥30 ng/mL. Positive DOAC Dipstick results should be confirmed by measuring DOAC plasma concentration.